PROJECT-BASED LEARNING APPROACH IN DEVELOPING LANGUAGE SKILLS: PRESETT EXPERIENCES - Mamirbaeva, D. Dj.; Jumamuratova, D. (SCIENCE and SOCIETY, 2023)
This article is devoted to the problems of implementing Project-based learning approach in teaching English for developing students’ language skills.